Liebermannite, KAlSi3O8, a new shock‐metamorphic, high‐pressure mineral from the Zagami Martian meteorite. (30th October 2017) - Ma, Chi; Tschauner, Oliver; Beckett, John R.; Rossman, George R.; Prescher, Clemens; Prakapenka, Vitali B.; Bechtel, Hans A.; MacDowell, Alastair
Abstract: In this paper, we discuss the occurrence of liebermannite (IMA 2013‐128), KAlSi3 O8, a new, shock‐generated, high‐pressure tetragonal hollandite‐type structure silicate mineral, in the Zagami basaltic shergottite meteorite. Liebermannite crystallizes in space group I 4 /m with Z  = 2, cell dimensions of a  =   9.15 ± 0.14 (1σ) Å, c  =   2.74 ± 0.13 Å, and a cell volume of 229 ± 19 Å 3 (for the type material), as revealed by synchrotron diffraction. In Zagami, liebermannite likely formed via solid‐state transformation of primary igneous K‐feldspar during an impact event that achieved pressures of ~20 GPa or more. The mineral name is in honor of Robert C. Liebermann, a high‐pressure mineral physicist at Stony Brook University, New York, USA.